2017
DOI: 10.1093/cid/cix081
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Laboratory Methods for the PERCH Study

Abstract: The Pneumonia Etiology Research for Child Health study was conducted across 7 diverse research sites and relied on standardized clinical and laboratory methods for the accurate and meaningful interpretation of pneumonia etiology data. Blood, respiratory specimens, and urine were collected from children aged 1–59 months hospitalized with severe or very severe pneumonia and community controls of the same age without severe pneumonia and were tested with an extensive array of laboratory diagnostic tests. A standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 23 publications
1
63
0
Order By: Relevance
“…Whenever incorporating ancillary diagnostics into a case definition, the equipment and technologies used should be thoroughly profiled and, ideally, standardised. 87,116 These factors are both particularly important when study personnel are not doing these ancillary tests or diagnostic procedures themselves, such as in passive surveillance. Investigators should aim to homogenise the equipment and diagnostic procedures available across health facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whenever incorporating ancillary diagnostics into a case definition, the equipment and technologies used should be thoroughly profiled and, ideally, standardised. 87,116 These factors are both particularly important when study personnel are not doing these ancillary tests or diagnostic procedures themselves, such as in passive surveillance. Investigators should aim to homogenise the equipment and diagnostic procedures available across health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should consider a standardised approach for both sample collection and laboratory processing, as described by PERCH investigators. 87 Studies that investigate the causes of pneumonia could help to reduce heterogeneity in pneumonia phenotypes by identifying whether the underlying infection is predominantly bacterial, viral, or a combination of both. One potential complication with these studies is that multiple pathogens are often found in the respiratory tract of both sick and healthy children.…”
Section: Aetiology Detectionmentioning
confidence: 99%
“…PERCH employed conventional and molecular diagnostic techniques for the identification of potential pathogens, as described elsewhere [8, 2831]. In brief, total nucleic acid extraction was performed on respiratory specimens using the NucliSens easy-MAG system (bioMérieux, Marcy l’Etoile, France).…”
Section: Methodsmentioning
confidence: 99%
“…All laboratory methods were standardized across sites [18]. A flocked NP swab (flexible minitip; Copan) and a rayon oropharyngeal (OP) swab specimen were collected from each case and control and were placed into the same vial.…”
Section: Specimen Collection and Laboratory Testingmentioning
confidence: 99%
“…A second NP specimen for S. pneumoniae culture was collected simultaneously with the first swab specimen; pneumococcal isolates were serotyped using Quellung reaction or latex agglutination, as described elsewhere [18]. Testing was performed at each site, and all sites participated in external quality assurance programs for both pneumococcal PCR and serotyping [18].…”
Section: Specimen Collection and Laboratory Testingmentioning
confidence: 99%